2009
DOI: 10.1210/en.2009-0578
|View full text |Cite
|
Sign up to set email alerts
|

Central Nesfatin-1 Reduces Dark-Phase Food Intake and Gastric Emptying in Rats: Differential Role of Corticotropin-Releasing Factor2 Receptor

Abstract: Nesfatin-1, derived from nucleobindin2, is expressed in the hypothalamus and reported in one study to reduce food intake (FI) in rats. To characterize the central anorexigenic action of nesfatin-1 and whether gastric emptying (GE) is altered, we injected nesfatin-1 into the lateral brain ventricle (intracerebroventricular, icv) or fourth ventricle (4v) in chronically cannulated rats or into the cisterna magna (intracisternal, ic) under short anesthesia and compared with ip injection. Nesfatin-1 (0.05 μg/rat, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
285
0
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(310 citation statements)
references
References 40 publications
10
285
0
15
Order By: Relevance
“…Most of the authors working on rats and using icv injections investigating different aspects of nesfatin-1's actions have also found the 5 --20 pmol dose range effective, higher doses only caused earlier timing of the effect, and/or enhanced the tendencies observed with lower dose. 5,22,23 We also found the 25 pmol dose as an adequate one, increasing the dose to 100 pmol did not lead to any substantially new observations. Long-lasting effects and interference with the diurnal rhythm are not exclusive among the peptides regulating energy balance.…”
Section: Discussionmentioning
confidence: 53%
“…Most of the authors working on rats and using icv injections investigating different aspects of nesfatin-1's actions have also found the 5 --20 pmol dose range effective, higher doses only caused earlier timing of the effect, and/or enhanced the tendencies observed with lower dose. 5,22,23 We also found the 25 pmol dose as an adequate one, increasing the dose to 100 pmol did not lead to any substantially new observations. Long-lasting effects and interference with the diurnal rhythm are not exclusive among the peptides regulating energy balance.…”
Section: Discussionmentioning
confidence: 53%
“…So far, only one study described the occurrence of mature nesfatin-1 peptide in the cerebrospinal fluid of rats, whereas in brain nuclei only full length NUCB2 was detected [24]. In all subsequent reports, only full length NUCB2 was detected by Western blot [8,27,36] or studies performing immunostaining did not distinguish between NUCB2 protein and nesfatin-1 peptide [5,6,8,10,13,14,16,18,25,32,34,42,43]. Since also full length NUCB2 exerts an anorexigenic effect it is also possible that this protein is the active circulating form.…”
Section: Discussionmentioning
confidence: 99%
“…NUCB2/ nesfatin-1 was described in rat brain food intake regulatory nuclei and implicated in the regulation of food intake [24]. Several studies reported a reduction of food intake following central injection of nesfatin-1 in mice and rats [2,21,24,32,45] and one study after peripheral injection in mice [29]. These effects are in opposition to those of ghrelin which is well established to stimulate food intake after central [41] as well as peripheral injection in rodents [41] and humans [40].…”
Section: Introductionmentioning
confidence: 99%
“…The possible involvement of the CRF2 receptors in the mediation of nesfatin-1's effect was investigated. The CRF2 antagonist, astressin2-B , injected intracerebroventricular completely abolished the dark phase food intake reduction induced by intracerebroventricular nesfatin-1 (Stengel et al, 2009). By contrast, a control peptide of similar structure as astressin2-B but without affinity to the CRF2 receptor did not influence intracerebroventricular nesfatin-1's action (Stengel et al, 2009).…”
Section: Nesfatin-1/nucb-2 and Anorexigenic Effectmentioning
confidence: 98%
“…The CRF2 antagonist, astressin2-B , injected intracerebroventricular completely abolished the dark phase food intake reduction induced by intracerebroventricular nesfatin-1 (Stengel et al, 2009). By contrast, a control peptide of similar structure as astressin2-B but without affinity to the CRF2 receptor did not influence intracerebroventricular nesfatin-1's action (Stengel et al, 2009). However as reported by Stengel et al (2009), astressin2-B injected intracerebroventricular did not modulate the rapid onset reduction of food intake observed after intracerebroventricular injection of nesfatin-1.…”
Section: Nesfatin-1/nucb-2 and Anorexigenic Effectmentioning
confidence: 98%